A review of the state of art and prospects in energy storage systems for energy harvesting applications - Sutikno, Tole; Arsadiando, Watra; Tan, Chee Wei; Facta, Mochammad (International Journal of Advances in Applied Sciences, 2024)
Due to the increasing trend in worldwide energy consumption, many new energy technology systems have emerged in the past decades. The implementation of energy storage system (ESS) technology in energy harvesting systems is significant to achieve flexibility and reliability in fulfilling the load demands. In this paper, several types of energy storage technologies available in the market are discussed to view their benefits and drawbacks. The main aim of this review is to provide a platform for readers especially those who seek to know more about ESS at a glance, to decide which ESS technology is best suited for any specific applications. This review would serve as a base for the initial state to make the right decision by referring to the criterias and characteristics of energy resources to get the optimal ESS technology. A comprehensive comparison among the various types of ESS technologies is outlined and elaborated to provide a better and clearer picture to the readers. Last but not least, the relevant recommendations and alternative choices for services related to the harvesting of solar PV energy are described too. It is hoped that the findings of this review article may be helpful to all readers interested in ESS technology.